Presentation is loading. Please wait.

Presentation is loading. Please wait.

2.5 The proofs of theorems 證明方法 p → q 與 p  q 之應用 Definition 2.8 Let n be an integer. We call n even if n is divisible by 2 - that is, if there exists.

Similar presentations


Presentation on theme: "2.5 The proofs of theorems 證明方法 p → q 與 p  q 之應用 Definition 2.8 Let n be an integer. We call n even if n is divisible by 2 - that is, if there exists."— Presentation transcript:

1 2.5 The proofs of theorems 證明方法 p → q 與 p  q 之應用 Definition 2.8 Let n be an integer. We call n even if n is divisible by 2 - that is, if there exists an integer r so that n=2r. If n is not even, then we call n odd and find for this case that there exists an integer s where n=2s + 1.

2 Direct proofs ( 直接證法 ) Indirect proofs ( 間接證法 ) Proofs by contradictions ( 矛盾法或歸謬法 ) Assumption Result Derived Direct p(m) q(m) ( 直接證法 ) Contraposition ¬q(m) ¬p(m) ( 間接證法 ) Contradiction p(m) and ¬q(m) F 0 ( 矛盾證法 )

3 The implication p  q can be proved by showing that if p is true, then q must also be true. This shows that the combination p true and q false never occurs. Theorem 2.3 (p114) For all integers m and n, if m and n are both odd, then their product mn is also odd. Direct proofs ( 直接證法 )

4 If m is an even integer, then m + 7 is odd. Proof: ( 直接證法 ) Since m is even, we have m=2a for some integer a. Then m + 7 = 2a + 7=2a + 6 + 1= 2(a + 3) + 1. Since a + 3 is an integer, we know that m + 7 is odd. THEOREM 2.4 p114

5 If m is an even integer, then m + 7 is odd. Proof: ( 直接證法 ) 1. 前提為真, m = 偶數, 即 m=2a , a 為整數. ( 偶數之定義 ) 2. m + 7 = 2a + 7=2a + 6 + 1= 2(a + 3) + 1. 其中 a + 3 為整數 3. ∴ m + 7 = 奇數 ( 奇數之定義 ) 結論為真 THEOREM 2.4 p114

6 If m is an even integer, then m + 7 is odd. Proof: ( 間接證法 ) Suppose that m + 7 is not odd, hence even. Then m + 7=2b for some integer b and m=2b − 7=2b − 8 + 1=2(b − 4) + 1, where b − 4 is an integer. Hence m is odd. [The result follows because the statements and are logically equivalent.] THEOREM 2.4 p114

7 If m is an even integer, then m + 7 is odd. Proof: ( 間接證法 ) 1. 若結論不為真,即 m + 7 不是奇數,而是偶數 2. m + 7=2b , b 為整數 ( 定義 ) m=2b − 7=2b − 8 + 1=2(b − 4) + 1, 其中 b − 4 為整數 3. ∴ m 為奇數 ( 定義 ) 4. 因 與 等價 ∴原定理成立 THEOREM 2.4 p114

8 If m is an even integer, then m + 7 is odd. Proof: ( 矛盾證法 ) THEOREM 2.4 p114 Assumption Result Derived Contraposition ¬q(m) ¬p(m) ( 間接證法 ) Contradiction p(m) and ¬q(m) F 0 ( 矛盾證法 )

9 If m is an even integer, then m + 7 is odd. p(m) and ¬q(m) F 0 ( 矛盾證法 ) 1)Now assume that m is even and that m + 7 is also even. 2)Then m + 7 even implies that m + 7 = 2c for some integer c. And, consequently, m =2c−7=2c−8+1= 2(c − 4) + 1 with c − 4 an integer, so m is odd. 3)Now we have our contradiction. We started with m even and deduced m odd—an impossible situation, since no integer can be both even and odd.

10 If m is an even integer, then m + 7 is odd. p(m) and ¬q(m) F 0 ( 矛盾證法 ) 1)Now assume that m is even and that m + 7 is also even. ( 假設 m 是偶數, 且 m+7 亦是偶數 ) 2) Then m + 7 even implies that m + 7 = 2c for some integer c. And, consequently, m =2c−7=2c−8+1= 2(c − 4) + 1 with c − 4 an integer, so m is odd. m+7 是偶數, 故 m+7=2c, 其中 c 是整數 m=2c-7=2c-8+1=2(c-4)+1, (c-4) 是整數 依奇數定義, m=2(c-4)+1 是奇數 3) Now we have our contradiction. m 是偶數, 又是奇數, 相互矛盾 所以 m+7 不可能是偶數

11 續上 How did we arrive at this dilemma? ( 困境, 兩難推理 ) Simple - we made a mistake! This mistake is the false assumption - namely, m + 7 is even - that we wanted to believe at the start of the proof. Since the assumption is false, its negation is true, and so we now have m+7 odd.

12 For all integers m and n, if m and n are both odd, then their product mn is also odd. ( 如果 m 和 n 都是奇數時, mn 一定是奇數。 ) Proof: (1) Since m and n are both odd, we may write m=2a + 1 and n =2b + 1, for some integers a and b – because of Definition 2.8. (2) Then the product mn =(2a + 1)(2b + 1)=4ab + 2a + 2b + 1=2(2ab + a + b) + 1, where 2ab + a + b is an integer. (3) Therefore, by Definition 2.8 once again, it follows that mn is odd. THEOREM 2.3 p114

13 THEOREM 2.5 (p115) For all positive real numbers x and y, if the product xy exceeds 25, then x > 5 or y > 5. Proof: 解 1 – 直接證明法 若 xy > 25, 則 ??? 似乎無法繼續下去 解 2 – 間接證法 或 矛盾證法

14 THEOREM 2.5 (p115) For all positive real numbers x and y, if the product xy exceeds 25, then x > 5 or y > 5. p(x, y) → q(x, y) Proof: 利用間接證明法 (1) 假設 “x > 5 或 y > 5” 不為真, 即 0 < x ≦ 5 且 0 < y ≦ 5. (2) 故 0 =0 · 0 <x · y ≦ 5 · 5 =25 (3) 即 “xy > 25” 不為真 (4) 因 ┐q → ┐p 與 p → q 等價, 所以原式成立

15 THEOREM 2.5 (p115) For all positive real numbers x and y, if the product xy exceeds 25, then x > 5 or y > 5. Proof: Consider the negation of the conclusion—that is, suppose that 0 < x ≦ 5 and 0 < y ≦ 5. Under these circumstances we find that 0 =0 · 0 <x · y ≦ 5 · 5 =25, so the product xy does not exceed 25. (This indirect method of proof now establishes the given statement, since we know that an implication is logically equivalent to its contrapositive.)


Download ppt "2.5 The proofs of theorems 證明方法 p → q 與 p  q 之應用 Definition 2.8 Let n be an integer. We call n even if n is divisible by 2 - that is, if there exists."

Similar presentations


Ads by Google